To find the equation of the linear function passing through these two points, we need to first determine the slope of the line.
Using the formula for the slope of a line:
m = (y2 - y1)/(x2 - x1)
Substitute the given points:
m = (3 - 1)/(-5 - (-3))
m = 2/-2
m = -1
Now that we have the slope, we can use the point-slope form of a linear equation to find the equation of the line.
y - y1 = m(x - x1)
Using the point (-3, 1):
y - 1 = -1(x + 3)
y - 1 = -x - 3
y = -x - 2
Therefore, the equation of the linear function passing through the points (-3, 1) and (-5, 3) is y = -x - 2.
Write an equation of the linear function that passed through the points (-3,1) and (-5,3)
1 answer